Laparoscopic Sentinel Node Mapping with Surgical Staging following Hysteroscopic Endometrial Resection in Endometrial Stromal Sarcoma - Wasinghon, Phornsawan; Lee, Chyi-Long (Gynecology Obstetrics & Reproductive Medicine, 2020)
A 50-year-old woman presented with symptoms of abnormal uterine bleeding. Ultrasonography showed an intrauterine cavity nodule sized approximately 2 cm. A hysteroscopic resection was diagnosed. The histopathology revealed high-grade endometrial stromal sarcoma. The surgery was laparoscopic surgical staging with indocyanine green sentinel lymph node mapping. Two positive indocyanine green sentinel lymph node of the right and left pelvic nodes showed no nodal metastasis. Also, the five positive indocyanine green sentinel lymph node showed no nodal metastasis. The occult lymph nodes were dissected at the right and left pelvic nodes for nodes 4 and 9, respectively. Conclusively, hysteroscopic resection is beneficial for the diagnosis of uterine sarcoma. Notwithstanding, laparoscopy can be used for uterine cancer and the indocyanine green sentinel lymph node showed no false negative. The patient was stage IA.